1980
DOI: 10.3758/bf03204457
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in support of word unitization

Abstract: In each of five experiments, the subjects viewed tachistoscopically presented pairs of letters and made speeded comparison judgments on the basis of name identity. On most trials, a noise letter string (word or anagram) was placed directly between the target letters. The results indicated that correct "same" RTs were a function of noise item type and its relation to target letters. Anagrams increased RTs more than their counterpart words, except when the noise word was either unmeaningful or response incompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…It may be the use of such inter letter or whole word pattern information that allows word code activation to be independent of letter code activation, as indicated in the present findings as well as those of O'Hara (1980).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It may be the use of such inter letter or whole word pattern information that allows word code activation to be independent of letter code activation, as indicated in the present findings as well as those of O'Hara (1980).…”
Section: Discussionsupporting
confidence: 72%
“…Such an argument has been raised by Johnson (1975), and recent support for the independence of letter and word perception has been reported by O'Hara (1980). He found that positioning unrelated letters between two letters to be matched slows down the response, but such interference is greatly reduced or even eliminated when the interpolated letters make up a familiar word.…”
Section: Discussionmentioning
confidence: 87%
“…A. Eriksen & C. W. Eriksen, 1974;C. W. Eriksen & Schultz, 1979;O'Hara, 1980) and have occurred in experiments in which the congruent and incongruent conditions were equated for stimulus-response compatibility (C. W. Eriksen & Schultz, 1979). Although stimulus-response incompatibility is not necessary for response competition to occur, the contribution of stimulus-response compatibility to response competition is not unexpected (Greenwald, 1970;Keele, 1973, chap.…”
Section: Verbalmentioning
confidence: 99%
“…It also permits us to determine whether there is a single circumscribed area that is attended or whether attention can be simultaneously concentrated on two separated locations in the visual field. The two forms constituting the target pair can be separated by varying distances in both the vertical and horizontal dimensions, and since same-different judgments have been shown to be quite sensitive to response-competition effects (C. W. Keren, O'Hara, & Skelton, 1977;Krueger, 1978;O'Hara, 1980;St. James & C. W. Eriksen, 1991), the extent or two-dimensional shape of the attended area can be assessed by probing the visual field at different locations with response-incompatible noise stimuli.…”
mentioning
confidence: 99%